Natural procreative technology (NaProTechnology) for infertility: take-home baby rate and clinical outcomes in a 5-year single-center cohort of 1,310 couples - Sánchez-Méndez, José Ignacio; Lombarte, María; Abengózar-Muela, Ricardo; Acosta-Díez, Juan; Alonso-Fernández, Patricia; Cañones-Castañón, María Pilar; Calderón-Ruiz, Olga; Espinosa-García, Elena; Galocha-Morgado, Carolina; Siegrist, Jaime; Alonso-Salvador, Sonsoles (Frontiers in Reproductive Health, 2025)
IntroductionAssisted reproductive technologies (ART) are widely used to address infertility; however, they are costly, associated with medical risks, and often yield suboptimal clinical outcomes. Natural Procreative Technology, also known as NaProTechnology (NPT), provides a systematic and integrative approach to infertility by thoroughly identifying and treating underlying medical conditions to restore the couple's natural fertility potential. Despite its promise, real-world data on NPT effectiveness remain limited. The objective of this study is to evaluate the take-home baby rate in a large population of infertile couples treated with NPT and to synthesize findings from previously published studies.MethodsA retrospective cohort study was conducted involving 1,310 infertile couples treated at a specialized fertility clinic in Spain over a 5-year period. Participants presented with primary or secondary infertility or recurrent pregnancy loss. Clinical data, diagnoses, and outcomes were analyzed, including surgical interventions and treatment duration.ResultsThe mean age of women and men was 35.0 (SD 4.4) and 36.9 (SD 5.3) years, respectively. Primary infertility was the most common subtype (73.5%), the median infertility duration was 24 months, and prior ART attempts were recorded in 27.5% of couples. Mean number of diagnoses per couple was 2.5 (SD 1.3). The crude take-home baby rate was 35.3% (N = 463). Independent predictors of successful take-home baby included female age, recurrent pregnancy loss as the reason for consultation, duration of infertility, and the presence of endometriosis, hormonal dysfunction, male factor, and endometrial disorders as diagnoses. Considering a median duration of NPT of 10.9 months (range 8.1–17.0), the adjusted cumulative take-home baby rate was 62.1%. Rates varied significantly by female age, with higher success observed in younger women: 83.7% at 18–30 years, 53.3% at 36–40 years, and 24.4% over 40 years. A sensitivity analysis was performed to assess the impact of dropout assumptions on cumulative pregnancy rates. Nearly one-third of patients underwent surgery, most commonly hysteroscopy and/or laparoscopy.ConclusionIn this cohort, NPT was associated with a notably high take-home baby rate in an infertile population with unfavorable prognostic factors, including advanced maternal age, prolonged duration of infertility, or previous failed attempts at conventional ART procedures.